Women Empowerment through Production and Online Marketing Training of Wingko Babat Based on Cassava in Baturono Village, Sukodadi, Lamongan - Yudiana Indriastuti; Herlina Suksmawati (Future Science)
Empowering women's groups is seen as one of the specific strategies to increase their abilities and potential. Empowering women in business as an effort to increase independence and internal strength of a woman. Empowering women can also help improve the welfare of families and communities. The women in the village of Baturono, Sukodadi, Lamongan have a great opportunity in exploiting the potential of the village, especially the production of Wingko Babat which is a special food from the area. Wingko Babat production business competition certainly requires them to have innovation to be able to compete in the market. Through community service activities with UPN